Cooperation and resistance: Negotiating rubber in upland Philippines. (August 2016) - Montefrio, Marvin Joseph F.
Abstract: The production of rubber has encountered varied reactions among upland smallholder populations in Asia—some have cooperated while others resisted. While the general scholarship on smallholder behavior vis-à-vis rubber production has extensively examined perspectives in political economy/ecology, few have studied the role of environmental constructions, discourses and practices in elucidating spatial politics associated with rubber. This paper offers a case of indigenous smallholders' varied response to rubber based on their multiple understandings of and practices in upland environments in the Philippines. Based on qualitative field research in one rubber-growing community in Palawan, findings suggest that many indigenous smallholders have consented the expansion of rubber production areas in fallow lands and shifting cultivation systems, but opposed expansion in tabooed forests inhabited by invisible entities. The multiple meanings indigenous populations accord to different environments correspond to variations in political reactions and land-use decisions on the ground, thus highlighting the nuances of cooperation in and resistance to boom crops production regimes. Highlights: Examines spatial politics involving rubber production in upland environments. Based on in-depth interviews and participant observation in Palawan, Philippines. Indigenous smallholders consented expansion of rubber in fallow lands. Many also opposed expansion of rubber in tabooed forests inhabited by invisible entities. Multiple environmental meanings correspond to variations in land-use decisions.